The Remote Audit and Information Technology: The impact of Covid-19 Pandemics - Nugrahanti, Trinandari Prasetyo; Pratiwi, Arvega Safina (Universitas Negeri Malang, 2023)
This study aimed to examine the effect of remote auditing and information technology on audit quality and professional ethics as moderating variables. It used a quantitative method with primary data obtained using a questionnaire. This research uses quantitative methods with primary data obtained through a questionnaire. This research population is auditors working in Public Accounting Firms around DKI Jakarta Province, Indonesia. A sample of 122 respondents was selected from the people using the convenience sampling technique. The results showed that remote auditing and information technology affected audit quality. Auditors work professionally by complying with audit standards to improve the quality of the results. Using information technology with computer-assisted audit techniques appropriately facilitates the auditors' process. The technology also makes data storage more effective and efficient, promoting quality audit work. Auditors should comply with professional ethics appropriate to the code of ethics of the public accounting profession.